PENINGKATAN KAPASITAS DALAM PENGELOLAAN DANA DESA DI DESA PADALUYU KECAMATAN TANGGEUNG KABUPATEN CIANJUR - Ristala, Harky; Permana, Danny (Jurnal Academia Praja, 2025)
This research aims to analyze the capacity of the administrative apparatus of Padaluyu Village in managing village funds, identify the factors influencing it, and formulate strategies for capacity enhancement. Law Number 3 of 2024 concerning Villages provides greater authority for villages in managing village funds. However, effective and accountable management of village funds requires adequate capacity from village officials. The enhancement of the capacity of village officials includes the development of knowledge, skills, and attitudes necessary for managing village funds effectively, efficiently, transparently, and accountably. The research method used is qualitative with a descriptive approach. The results of the study indicate that the capacity of the administrative apparatus of Padaluyu Village in managing village funds still needs to be improved. The factors influencing the capacity of village officials include knowledge, skills, mental attitudes, and ethics. Efforts to enhance the capacity of village officials can be carried out through training, mentoring, comparative studies, and the utilization of information technology.